A simple, safe and robust system for hydrogenation "without high-pressure gases" under batch and flow conditions using a liquid organic hydrogen carrier. Issue 5 (8th February 2022) - Porcar, Raul; Mollar-Cuni, Andrés; Ventura-Espinosa, David; Luis, Santiago V.; García-Verdugo, Eduardo; Mata, Jose A.
Abstract : A simple, safe and robust system for the continuous, in situ and on demand hydrogen generation under mild conditions. The highly pure hydrogen generated can be used for further hydrogenation reactions under both batch and continuous flow conditions. Abstract : A simple, safe and robust system for the continuous, in situ and on demand generation of hydrogen under mild conditions is reported. A device formed by a packed bed reactor containing a ruthenium N-heterocyclic carbene complex [Ru(arene)(Cl)2 (NHC)] supported onto graphene (NHC-Ru-rGO ) and a liquid–gas separator allows the continuous generation of hydrogen produced by the dehydrogenative coupling of silanes and alcohols under mild and safe conditions. The highly pure hydrogen generated can be used for further hydrogenation reactions under both batch and continuous flow conditions.